Investigating SO2 transfer across the air-water interface via LIF - Friman, Sonja I.; Jähne, Bernd (Experiments in fluids, 2019)
A laser-induced fluorescence technique to measure vertical concentration profiles of the tracer sulfur dioxide above the air-water interface is presented. The imaging technique is capable of recording profiles at a rate of up to 40 Hz with a sufficiently high spatial resolution to resolve the profile within the viscous boundary layer in the air at the air-water interface. The new technique was tested in a small wind-wave facility under invasion conditions with an initial concentration of 100 ppm in the air at estimated wind speeds u10u10u_{10} of 0.7-3 m/s, corresponding to friction velocities between 2.4 and 9.3 cm/s. The laser used for fluorescence excitation has a wavelength of 223.7 nm. In this work, a proof of principle is presented as well as a first evaluation of the capabilities and uncertainties of the technique. The new technique enables a detailed study of the transport processes in the air-sided boundary layer at a wavy interface including the gas transfer velocity, turbulent concentration fluctuations, and the partitioning of gas transfer between air and water.Graphical abstract Open image in new window